The Effect of Environmental Performance and Green Accounting on Firm Value - Fikriyah, Siti Hailatul; Wiyanti, Rahma (EAJ (Economic and Accounting Journal), 2023)
Both large corporations and small and medium-sized businesses frequently ignore environmental problems. However, environmental accounting, known as "Green accounting," has recently gained popularity. The industry and the green movement are coming to terms with the critical idea of sustainable development. Improved natural resources and green accounting will provide essential insights into the environment and business interaction. However, green accounting implementation in organizations purposes for various reasons, including a need for knowledge, ethics education, et cetera. The study samples were collected using purposeful sampling and analyzed using quantitative data. According to the findings of this study, green accounting and environmental performance have a significant impact on firm value.